Quick serve restaurant (QSR) in petronas mesra convenience store and its acceptance by Malaysian consumers in regards to their lifestyle - fast food preferences. / Khairul Hisham Mazlan - Mazlan, Khairul Hisham (1998)
The study focuses on the consumers’ acceptance towards the implementation of QSR in regards to lifestyle preference. It is to determine and examine the acceptance of consumers towards the concept. Since the concept is newly adopted from United States, the problem of the suitability between consumers’ lifestyle and QSR had arouse the researcher’s interests to explore and study the consumers’ acceptance. As to support the study, the researcher had studied on consumers’ acceptance, lifestyle and the QSR from the references, journals and other sources to be included in the literature review. This is purposely to get more knowledge about the topic studied. Furthermore, from the constructed objective of the study, the researcher had state and formulizes four hypotheses. This is to determine whether the researcher’s theory/belief about consumers’ lifestyle and acceptance of QSR have a relationship by using independent variables (time preferred, place preferred, acceptance of features and reason of preferring QSR) and the dependent variable (acceptance of QSR). These hypotheses were tested and analyzed using the validity technique and the Pearson method. Hence the result had shown that the hypotheses were significant and each of the variable have a relationship on each other. The findings have resulted that majority of the respondent are not accepting QSR as their fast food preference because of they are still prefer to eat in the restaurant, and this is very contra to the concept where it encouraging people to takeaway.